Clock Reactions: A Kinetic Study of Sulfur and Iodine Systems - Li, Haoxuan (Transactions on Environment, Energy and Earth Sciences, 2026)
This study presents a kinetic investigation of two classic clock reactions: the sulfur clock (sodium thiosulfate and hydrochloric acid) and the iodine clock (persulfate and iodide ions). The main goal was to establish the rate law for each system by systematically changing the concentrations of the reactants. For the sulfur clock reaction, a graphical analysis plotting initial rate against thiosulfate concentration strongly suggested a first-order relationship with respect to , yielding the rate law: Rate = 0.356[ ]. In the case of the iodine clock reaction, a pseudo-order approach coupled with logarithmic analysis was used to effectively isolate the kinetic influence of each reactant. The results from this experiment indicate that the reaction is first-order with respect to both persulfate  and iodide I−ions. Consequently, the overall rate law was determined to be Rate = k[ ][I−], and the rate constant (k) was calculated to be approximately 3.63 × 10⁻³ M⁻¹s⁻¹. Ultimately, this work not only confirms the established kinetics of these reactions but also demonstrates the practical utility of initial rate methods in a high school laboratory setting.
Keywords: Chemical kinetics; clock reaction; rate law; reaction order; pseudo-order method; initial rates.